Simulation Testing of Hormonic Reduction in SHPF-TCR Compensator in Comparison with Steady State Response and Dynamic State Response - Lakshmi, B.Prasanna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This paper proposes the implementation of the comparative analysis of the with conventional power system arrangement to the steady state and dynamic state of the a combined system of a Thyristor-controlled reactor (TCR) and a shunt hybrid power filter (SHPF), for the process of limiting the total harmonic reduction is proposed in this paper. Total Circuit Configuration Is Simulated Using MATLAB 2012a And It Is Analyzed In Power Graphical User Interfacing Environment And The Total Harmonic Distortion Is Calculated By The Use Of The Fast Fourier Transformation Technique In POWERGUI,